The Impact Of Business Process Reengineering (BPR) On Organizational Performance Efficiency In Financial Services Organizations"Field Study In The Syrian Financial Services Sector" (Damascus University Journal for the economic and Political sciences, 2026)
Service organizations in a competitive business environment are under increasing pressure to deliver services quickly and efficiently, and BPR can be a valuable tool for improving speed, performance and customer satisfaction by radically redesigning organizational processes and achieving significant improvements in speed, quality and cost in the context of change management.This study examines the impact of administrative process reengineering on the efficiency of organizational performance in financial services organizations. A cross-sectional study was conducted through 74 responses in the headquarters of Syrian financial services sector organizations, and the results of the study showed that there is a significant positive effect linking the variables studied. Organizations that adopted administrative process reengineering were able to significantly reduce the time it takes to provide services, and they also witnessed a fundamental improvement in organizational performance measured through the dimensions of administrative process reengineering (renewal, automation, and networking of processes).The results of this research indicated that business process reengineering can be a valuable tool for improving speed, performance, and customer satisfaction in service organizations when applied systematically. Organizations looking to improve customer service and bottom-line results of operations are advised to consider adopting business process reengineering along the dimensions measured in this research. The researcher also recommends more longitudinal studies that address these variables in different sectors and other organizational aspects to identify their impact.
Keywords: Business Process Reengineering; Change management; Performance evaluation; Financial Services Organizations